Loss to Follow-up in Adolescent and Young Adult Renal Transplant Recipients. Issue 6 (June 2021) - Melanson, Taylor A.; Mersha, Karie; Patzer, Rachel E.; George, Roshan P.
Abstract : Background: Patients' loss to follow-up (LFU) has significant impacts on outcomes and is a barrier to improving care, especially in adolescent and young adult (AYA) renal transplant recipients. There is limited information regarding the relationship between transfer of care from pediatric to adult transplant centers, age, and LFU among AYA renal transplant recipients. Methods: We studied 16 386 individuals aged 10–29 years who received kidney transplants between January 1, 2005 and December 31, 2015 using the Scientific Registry of Transplant Recipients. The primary outcome was LFU, which was defined as >1 year without follow-up in a transplant clinic/program. Death or graft failure within a year of the last follow-up was not classified as LFU. We performed a retrospective cohort study describing LFU using Pearson's chi-square tests. Multivariable logistic regression was used to estimate the change in likelihood of LFU associated with recipient characteristics and institution transfer. Results: In total, 22.26% (n = 3647) of our study population met criteria for LFU. About 11.17% (n = 1830) transferred institutions during the study period. LFU occurred in 50.18% of recipients who transferred institutions. LFU peaked at the age of 20 years, with 7.4% of 20-year-olds having LFU. The odds of LFU among renal transplant recipients who transferred institutions were 3.36 times greater (95% confidence interval, 3.1-3.6) than the odds of LFU among those who did not transfer institutions. Conclusions: LFU is a critical problem faced by AYA renal transplant recipients, and institution transfer is a significant risk factor for LFU. Additional studies investigating the interplay between age, institution transfer, and LFU in the AYA population are still needed.